2015
DOI: 10.1007/s10753-015-0181-6
|View full text |Cite
|
Sign up to set email alerts
|

Astragalin Attenuates Allergic Inflammation in a Murine Asthma Model

Abstract: The present study aimed to determine the protective effects and the underlying mechanisms of astragalin (AG) on ovalbumin (OVA)-induced allergic inflammation in a mouse model of allergic asthma. Our study demonstrated that AG inhibited OVA-induced increases in eosinophil count; IL-4, IL-5, IL-13, and IgE were recovered in bronchoalveolar lavage fluid, and increased IFN-γ level in bronchoalveolar lavage fluid. Histological studies demonstrated that AG substantially inhibited OVA-induced eosinophilia in lung tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…The role of LTC 4 in allergic asthma has been extensively evaluated (85). LTC 4 is produced in mast cells by assembly of a biosynthetic complex at the nuclear envelope, consisting of cytosolic phospholipase A2 (cPLA2), (64) Oxi-CaMKII inhibitor KN-93 KN-93 significantly decreased goblet cell hyperplasia, bronchial epithelial thickness, airway eosinophilia, the eosinophil chemoattractant molecule, Ccl-11, and NF-κB activity in allergic asthma (61) Leukotriene C4 (LTC 4 ) inhibitor A LTC 4 inhibitor reduced NOX4 levels and attenuated cell death (32) Galangin Galangin demonstrated decreased airway remodeling, angiogenic activity, and ASMC proliferation through the TGF-β1-ROS-MAPK pathway (65)(66)(67) Astragalin Astragalin suppressed LPS-induced ROS production and eotaxin-1 expression in epithelial cells through the TLR4-PKCγ1-PKCβ2-NADPH signaling pathway (68,69) Glutathione GSH balances Th1/Th2 responses, alters nitric oxide metabolism and inhibits ROS (55,59,70) SOD SODs protects against the harmful effects of ROS and airway inflammation (71)(72)(73) Glutathione peroxidases Glutathione peroxidases prevent airway inflammation and alveolar destruction (74)(75)(76) Vitamins C and E Vitamins C and E reduce AHR, inflammation, and oxidative stress (77)(78)(79) TLR7, toll-like receptor 7; Oxi-CaMKII, oxidative-CaMKII; SOD, superoxide dismutase; AHR, airway hyper-reactivity; Nrf2, nuclear factor E2-related factor 2; Cu/Zn SOD, copper/zinc superoxide dismutase; ROS, reactive oxygen species; NOX4, NADPH oxidase 4; LPS, lipopolysaccharide; Th2, type 2 helper T.…”
Section: Ltc 4 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of LTC 4 in allergic asthma has been extensively evaluated (85). LTC 4 is produced in mast cells by assembly of a biosynthetic complex at the nuclear envelope, consisting of cytosolic phospholipase A2 (cPLA2), (64) Oxi-CaMKII inhibitor KN-93 KN-93 significantly decreased goblet cell hyperplasia, bronchial epithelial thickness, airway eosinophilia, the eosinophil chemoattractant molecule, Ccl-11, and NF-κB activity in allergic asthma (61) Leukotriene C4 (LTC 4 ) inhibitor A LTC 4 inhibitor reduced NOX4 levels and attenuated cell death (32) Galangin Galangin demonstrated decreased airway remodeling, angiogenic activity, and ASMC proliferation through the TGF-β1-ROS-MAPK pathway (65)(66)(67) Astragalin Astragalin suppressed LPS-induced ROS production and eotaxin-1 expression in epithelial cells through the TLR4-PKCγ1-PKCβ2-NADPH signaling pathway (68,69) Glutathione GSH balances Th1/Th2 responses, alters nitric oxide metabolism and inhibits ROS (55,59,70) SOD SODs protects against the harmful effects of ROS and airway inflammation (71)(72)(73) Glutathione peroxidases Glutathione peroxidases prevent airway inflammation and alveolar destruction (74)(75)(76) Vitamins C and E Vitamins C and E reduce AHR, inflammation, and oxidative stress (77)(78)(79) TLR7, toll-like receptor 7; Oxi-CaMKII, oxidative-CaMKII; SOD, superoxide dismutase; AHR, airway hyper-reactivity; Nrf2, nuclear factor E2-related factor 2; Cu/Zn SOD, copper/zinc superoxide dismutase; ROS, reactive oxygen species; NOX4, NADPH oxidase 4; LPS, lipopolysaccharide; Th2, type 2 helper T.…”
Section: Ltc 4 Inhibitorsmentioning
confidence: 99%
“…Histological studies demonstrated that astragalin substantially inhibited OVA-induced eosinophilia in lung tissue. All of these anti-inflammatory roles may occur through suppression of cytokine signaling (SOCS)-3 and enhancement of SOCS-5 expression in an asthma model (68).…”
Section: Astragalinmentioning
confidence: 99%
“…In addition, Ast can reduce acute lung injury in a murine asthma model and enhance survival from lethal endotoxemia [21]. Also, Ast has anti-allergic and anti-oxidant activities [22,23]. Nevertheless, the clinical applications of Ast are still limited because it has low water solubility.…”
Section: The Activation and Differentiation Of Th Cells Distinguishementioning
confidence: 99%
“…It has been reported to have various pharmacological effects including anti-oxidant, anti-HIV, anti-allergic, and anti-inflammatory activities[21][22][23]. Although astragalin has one glucosyl unit at the C-3 position of the flavonoid C-ring, it has low water solubility.…”
mentioning
confidence: 99%
“…In addition, Ast can reduce acute lung injury in a murine asthma model and enhance survival from lethal endotoxemia [ 20 ]. Additionally, Ast has anti-allergic and anti-oxidant activities [ 21 , 22 ]. Nevertheless, the clinical applications of Ast are still limited because it has low water solubility.…”
Section: Introductionmentioning
confidence: 99%